Les chemins de fer en Afrique subsaharienne, entre passé révolu et recompositions incertaines - Roland Pourtier (Belgeo)
African railroads have been the most emblematic transport infrastructures at the time of colonization, allowing control over territories, access to landlocked spaces, export of raw materials. However, if we except South Africa, they reflect the colonial break-up and do not constitute true networks. Today they have to compete with road transport, which spells death for many lines. Comparative advantages of rail are only found in the transport of heavy or non perishable goods, as shown in the multimodal organisation of transports in the development corridors. Ore railroads offer the best prospects in a context of increasing ore production. The future of railroads is therefore at issue between territorial planning and mining outlet.